Quick Evaluation Study on Fourteen (14) Major Development Programmes in Latehar District of Jharkhand State Affected by Left Wing Extremism (LWE) - Planning Commission (Planning Commission, 2011)
"OVERVIEW OF THE REPORT A “Quick Evaluation Study on 14 Major Development Programmes in Five (05) Districts of Jharkhand State affected by Left Wing Extremism (LWE)”, was entrusted to XISS, Ranchi by the Programme Evaluation Organisation, Planning Commission, Government of India. As per requirement, the contract was signed between Programme Evaluation Organisation', Planning Commission, Government of India and XISS for conducting the study in five Districts in Jharkhand State and the study was conducted with reference to the terms of reference (ToR) and guidelines provided by the said organization. The facts and figures presented here are without any precondition or prejudice. EXECUTIVE SUMMARY (FINDINGS OF THE STUDY) 1.2.1 OVERVIEW OF THE REPORT A “Quick Evaluation Study on 14 Major Development Programmes in Five (05) Districts of Jharkhand State affected by Left Wing Extremism (LWE)”, was entrusted to XISS, Ranchi by the Programme Evaluation Organisation, Planning Commission, Government of India. As per requirement, the contract was signed between Programme Evaluation Organisation, Planning Commission, Government of India and XISS for conducting the study in five Districts in Jharkhand State and the study was conducted with reference to the terms of reference (ToR) and guidelines provided by the said organization."
"Programme Evaluation Organisation Planning Commission Government Of India New Delhi"